Mining Of Resource Usage Using Evoc Algorithm In Grid Environment. - Kee, Sim Ee; Chan, Huah Yong; Haron, Fazilah (2007)
This paper addresses the new algorithm namely Evolving Clustering (Evoc A1goritbm) which is an improved version of Evolving Clustering Method (ECM). The algorithm bas been evaluated using three main criteria; that is dynamicity, accuracy and the ability to identify the stable cluster members.